"This is not the place to bother people about BTS": Pseudo-synchronicity and interaction in timed comments by Hallyu fans on the video streaming platform Viki. (April 2023) - Locher, Miriam A.; Messerli, Thomas C.
Highlights: Consensual and conflictual interaction can be carried out in asynchronous timed comments. Conflictual interaction concerns non-drama oriented, platform-usage and ad-hominem attacks. Conflictual interactions can have a socializing function. Viewers acknowledge pseudo-synchronicity and develop ways to manage it. Abstract: The community of users on Viki.com, a video streaming platform distributing Asian television to an international audience, use the site to engage with streams of television dramas. Rather than just being passive consumers, viewers interact in a range of different ways, among them the use of Timed Comments (TC). TCs are comments viewers post while viewing dramas. Subsequent viewers can read these comments when streaming the same episode. Users can read and respond to comments by previous viewers as if they were written at the time of watching (similar to Danmaku). Building on our previous work on Viki-TCs, we have framed the community mainly as a harmonious collective engaging with artefacts from a different cultural and linguistic context. In this study, we focus on the creation of pseudo-synchronicity by looking at interactivity between TC writers and in particular on those TCs that construct conflict. Our corpus consists of 320, 000 multilingual, but predominantly English comments. We make use of an exhaustively annotated sample of 8, 930 comments to extract and formalize patterns of implicit and explicit interaction and locate them in the larger corpus using corpus linguistic methods. Special attention is given to conflictual interaction in connection with plot spoilers, judgments on co-viewers' analytic and experiential skills and inappropriate language usage, negative comments on actor appearance, commenters using the space for fan interaction outside of the drama-scope and the technical use of the platform. These conflictual interactions often function as negotiations of the platform norms, socialize viewers into how the space works and can thus also be linked to community building. Our study contributes to understanding better how online fan community norms are built and behavior is sanctioned or (implicitly) condoned through interaction. In this way we contribute both to the study of interaction in a context that works online and asynchronously and to the study of online fan communities.